2023
DOI: 10.1038/s41388-022-02588-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal view of malignant histogenesis and macroevolution via formation of polyploid giant cancer cells

Abstract: To understand how malignant tumors develop, we tracked cell membrane, nuclear membrane, spindle, and cell cycle dynamics in polyploid giant cancer cells (PGCCs) during the formation of high-grade serous carcinoma organoids using long-term time-lapse imaging. Single cells underwent traditional mitosis to generate tissue with uniform nuclear size, while others formed PGCCs via asymmetric mitosis, endoreplication, multipolar endomitosis, nuclear fusion, and karyokinesis without cytokinesis. PGCCs underwent restit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 62 publications
(86 reference statements)
2
7
0
Order By: Relevance
“…The endoreplication cycle eventually resulted in the development of PGCCs (mostly mononucleated PGCCs). Here, we found that PGCCs divided into daughter cells through diverse variants of mitosis, such as multipolar mitosis and RMEM as we recently reported ( 22 ). These aberrant mitoses generated multiple micronuclei and inevitably increased chromosomal instability, genomic chaos, and cancer macroevolution ( 22 , 39 , 52 , 53 ), which is known to contribute to chemotherapy resistance ( 54 , 55 ).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The endoreplication cycle eventually resulted in the development of PGCCs (mostly mononucleated PGCCs). Here, we found that PGCCs divided into daughter cells through diverse variants of mitosis, such as multipolar mitosis and RMEM as we recently reported ( 22 ). These aberrant mitoses generated multiple micronuclei and inevitably increased chromosomal instability, genomic chaos, and cancer macroevolution ( 22 , 39 , 52 , 53 ), which is known to contribute to chemotherapy resistance ( 54 , 55 ).…”
Section: Discussionsupporting
confidence: 77%
“…S4E and movie S8). In addition, during division, PGCCs can undergo restitution multipolar endomitosis (RMEM) ( 22 ), resulting in a massively fragmented multinucleated PGCC (Fig. 4D, fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations